Decolorization and Biodegradation of basic violet dye by fungal- bacterial consortia - Deivasigamni, Manimaran Rajavelu; Ramalingam, P. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The present study was aimed to test the ability of Penicillium citrinum MTCC 8009, Aspergillusterreus MTCC 3006, Bacillus cohnii and their consortia to decolorize basic violet dye. Different parameters such as initial dye concentration, dye to inoculum ratio and period of incubation were studied for the decolourization of the dye. The developed fungal-bacterial consortia exhibited maximum percent decolorization (92%) ability when compared to the treatment of dyes by individual microbes. Percent decolorization of basic violet dye (92%) was more efficient using fungal-bacterial (Penicillium citrinum and Bacillus cohnii) consortia than with individual cultures. Phyto-toxicity results indicated that bacterial-fungal consortia (Penicillium citrinum and Bacillus cohnii) treatmentÂ  was believed to degrade the dyes to non-toxic intermediates. The FTIR analysis also revealed that decolorization of basic violet dyes was due to its degradation.